Anatomical variations and their association with carpal tunnel syndrome: a comparison with healthy controls - Gruber, Michaela; Wawrik, Agnes; Gasser, Florin; Ebner, Barbara; Reitbauer, Philipp; Uzel, Robert; Poupardin, Rodolphe; Mahrhofer, Maximilian; Weitgasser, Laurenz; Schwaiger, Karl; Schaffler, Gottfried; Wechselberger, Gottfried; et al. (International orthopaedics, 2025)
Purpose The prevalence of carpal tunnel syndrome (CTS) as the foremost upper extremity entrapment neuropathy is well-documented. The present study aimed to evaluate the prevalence of anatomical variations in the carpal tunnel and their potential role as risk factors for CTS. Methods Data from 447 CTS patients who underwent median nerve decompression between 2018 and 2019 were retrospectively analyzed. As a control group, 200 hands from 103 age- and sex-matched asymptomatic volunteers were further investigated. Results Anatomical variations identified through ultrasound in 19.7% of CTS hands and 16.0% of controls. Specifically, 10.3% of CTS hands had persistent median arteries, while 14.3% had bifid median nerves. Both variations occurred in 4.9% of CTS patients. In the control group, 13.0% had persistent median arteries and 11.0% had bifid median nerves, with both found in 8.0%. Conclusions Anatomical variations were found in both, CTS patients and controls, but their prevalence did not differ significantly between groups, suggesting they are not independent risk factors for CTS.